2009
DOI: 10.1007/s00431-009-0997-x
|View full text |Cite
|
Sign up to set email alerts
|

Titration of betaine therapy to optimize therapy in an infant with 5,10-methylenetetrahydrofolate reductase deficiency

Abstract: Betaine therapy was given for 2 years to a 2-year-old boy with 5,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…Plasma betaine levels indicated satisfactory intestinal absorption of betaine (data not shown). Nevertheless, although little is known about betaine pharmacokinetics (Schwahn et al 2003), more frequent dosing of orally administered betaine (six divided doses) normalized tHCy levels in a infant with MTHFR deficiency, even before 1 year of age (Ucar et al 2010). 5.…”
Section: Available Treatmentsmentioning
confidence: 97%
“…Plasma betaine levels indicated satisfactory intestinal absorption of betaine (data not shown). Nevertheless, although little is known about betaine pharmacokinetics (Schwahn et al 2003), more frequent dosing of orally administered betaine (six divided doses) normalized tHCy levels in a infant with MTHFR deficiency, even before 1 year of age (Ucar et al 2010). 5.…”
Section: Available Treatmentsmentioning
confidence: 97%
“…The knowledge about betaine pharmacokinetics is limited (Schwahn et al 2003). It has been suggested that frequent administration of a moderate dose may provide clinical and biochemical benefit (Ucar et al 2010). Betaine or OHCbl alone may not result in sufficient metabolic control, but they seem to have synergistic effects (Bartholomew et al 1988).…”
Section: The Effects Of Treatment On Clinical Outcomementioning
confidence: 99%
“…There have been some reports describing the use of folic acid (5–80 mg/day) with good (Al Tawari et al 2002; Munoz et al 2015) or poor (Holme and Ronge 1989; Ucar et al 2010) response. A dose–response relationship was not observed (Holme and Ronge 1989).…”
Section: The Effects Of Treatment On Clinical Outcomementioning
confidence: 99%
“…Hastamız-da klinik, biyokimyasal ve MRI verileri neticesinde MTHFR eksikliğinden şüphe edilerek periferik kan DNA analizi Hollanda'dan VU Üniversitesi Medikal Merkezi Metabolizma Laboratuvarı'nda çalıştı-rılmıştır. Daha önce rapor edilmiş bir missense mutasyon olan c.1015T>G (p.trp339Gly) mutasyonu hastamızda homozigot olarak saptanmıştır (9,10). Tanıyı doğrulamak adına anne ve babanın c.1015T>G için heterozigot taşıyıcı oldukları göste-rilmiştir.…”
Section: Introductionunclassified